The Smartest Animals on the Planet : Extraordinary Tales of the Natural World's Cleverest Creatures. - Boysen, Sally (Bloomsbury Publishing Plc, 2009)
Thisriveting book, written by one of the world's authorities in thisfield, brings together the most recent and remarkable global researchrelating to almost every ""smart"" species.